Percepción de la imagen corporativa de la universidad técnica de cotopaxi en la comunidad estudiantil. - Pastas Taco, Karina Vanesa (2019)
The Cotopaxi, Technical University institution of Higher Education works for being the pioneer in quality education at the service of the young people of the country to train them in a high academic, scientific and professional level. The corporate image of the educational institution has been built on the social imaginary of those who make it up for a proactive of progress, taking into account that at present the corporate image is the fundamental pillar of an organization enterprise institution, for this reason the need to know how they are being seen by their audiences and be able to distinguish it from others, through different elements such as behavior, communication and symbolism. The research framed as the main objective of the study to examine the perception that the students have about the corporate image of the Cotopaxi Technical University, because at the moment, it has served so that the institution is identified in its quality and excellence. The methodology used to fulfill the stated objective was defined by means of a non-experimental transverse descriptive type design of a quantitative nature, using the survey technique, represented statistically. The sample frame was formed by a certain group of students from the careers that make up the Faculty of Human Sciences and Education of the Cotopaxi Technical University through probabilistic sampling. The results show the diverse perceptions of the corporate image of the Cotopaxi Technical in the students surveyed. Finally, it is concluded that the importance of institutional and academic image through the different tangible and intangible elements manifested through multiple channels need to be reinforced mainly in terms of visual identity (logo) and culturally in issues related to organizational performance and Customer Support.